2016
DOI: 10.5120/ijca2016912550
|View full text |Cite
|
Sign up to set email alerts
|

Detection of sink Hole Attack in Wireless Sensor Network using Advanced Secure AODV Routing Protocol

Abstract: ABSTRACTwireless sensor network has been used for data sensing and collection at a single point for decision making process. Attack comprising in WSN produced various issues in data transmission and data management. Sinkhole attack is a compromised attack in WSN that compromised nodes that advertises a shortest path for data transmission. In this paper a new approach has been purposed for detection of sinkhole compromised nodes available in the network. On the basis of simulation results we can see that purpos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…To alleviate it MAC has been playing decisive role, especially towards better resource allocation, reliable transmission and data security. The existing approaches address security concerns in two distinct manners, first routing-based security and second MAC based security for which different efforts have been made [12][13][14][15][16][17][18][19][20][21][22][23]. As routing-based solutions, authors [12] designed dual-attack detection model for black-and-Gray hole attack resilience.…”
Section: Related Workmentioning
confidence: 99%
“…To alleviate it MAC has been playing decisive role, especially towards better resource allocation, reliable transmission and data security. The existing approaches address security concerns in two distinct manners, first routing-based security and second MAC based security for which different efforts have been made [12][13][14][15][16][17][18][19][20][21][22][23]. As routing-based solutions, authors [12] designed dual-attack detection model for black-and-Gray hole attack resilience.…”
Section: Related Workmentioning
confidence: 99%
“…Routing and MAC layers are vulnerable to various attacks in MANET. According to security threats in MANET, researchers 42–53 have proposed different solutions for MANET. We, first, classify the previous work into three subsections.…”
Section: Related Workmentioning
confidence: 99%
“…To control the CAA attacks, the authors proposed more than one methods such as fair MAC protocol, introducing protecting traffic flow and adjusting distance. Gupta et al 50 suggested a hybrid approach to detecting sinkhole attack using the TDMA MAC protocol in the wireless sensor network (WSN). They used destination sequence number and one-hop mechanism for detecting the attacker in a network.…”
Section: Related Workmentioning
confidence: 99%